Transformation of the Ancestor of the Roman Languages How to Convert It into New Roman Languages - Gandomi, Nasrin (LANGUAGE ART, 2022)
When a language is spoken in a very wide area, it changes, but the changes observed in one geographical area are different from the changes of that language in another area. Hence, an old single language appears in different forms in the next stage. The famous example of this is the ancestor of the roman language, the roman, and the derived languages, the new roman. These new languages are still similar in cases, but are not mutually reinforcing. In this article, in the historical survey of the ancestor of the romance languages, it is shown that this language has never died but is continuous and has been created by the diversity of language that has been done by companionship with other languages. The various forms of the Latin language used today in Paris, Rome, and Madrid, though different from Roman, but derived from the ancestor of the Roman language, and now instead of Latin Paris, Rome and Latin Madrid are used as French, Italian and Spanish. Also in this paper, by studying the branch of Italic language from large family of Indo-European languages, and studying the most important language among the languages of this branch, which is undoubtedly Latin, it tried to trace the traces of this language among the languages of that branch.